Highly durable Li-ion battery anode from Fe3O4 nanoparticles embedded in nitrogen-doped porous carbon with improved rate capabilities - Deshmukh, Ashvini B.; Dwivedi, Pravin K.; Nalawade, Archana C.; Qureshi, Mohammed S.; Shelke, Manjusha V. (Journal of Materials Science, 2020)
For next generation, lithium-ion batteries (LIBs) developing high capacity anode materials are crucial with increasing demand of large-scale application. Conversion-type anode materials are promising if stable cycling behavior could be achieved. In this work, a nitrogen-doped porous carbon-Fe3O4(NPC-Fe3O4) nanocomposite is synthesized via a simple and scalable approach. Composite is prepared by pyrolysis of polymer silica hybrid PolyHIPE (high internal phase emulsion) into NPC, and Fe3O4 nanoparticles (NPs) are anchored on its surface via hydrothermal synthesis. As-prepared NPC-Fe3O4 nanocomposite delivers high reversible capacity of around 1001 mAhg(-1)at 0.1 Ag-1 current density and rate capabilities and displays excellent cycling stability as high as 95% capacity retention even after 400 cycles. Superior electrochemical performance of NPC-Fe3O4 is attributed to the hierarchical porous structure and nitrogen doping of carbon which shorten the diffusion path of Li+ and provide ample space to prevent aggregation of Fe3O nanoparticles. [GRAPHICS] .

High efficiency lithium storage in 3D composite foam of Co3O4 nanoparticles integrated carbon nanohorns - Dwivedi, Pravin K.; Parte, Golu; Thripuranthaka, M.; Shelke, Manjusha V. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2021)
A well-designed 3 dimensional (3D) nanocomposite foam of Co3O4 nanoparticles and functionalized carbon nano horns (CNH) is prepared by feasible wet chemistry followed by lyophilization. This 3D nanocomposite foam is evaluated electrochemically as anode material for lithium-ion battery (LIB). 3D hierarchical mesoporous hybrid of functionalized carbon nano horn-Co3O4 (CCO) shows excellent lithium storage properties with long cycle life due to high surface area, good conductivity, 3D interconnected mesoporous structure, mechanical and chemical stability and shortened diffusion path length for Li+ ions during lithiation-delithiation. The Co3O4 nanoparticles incorporated into interconnected CNH foam effectively increases the number of active sites of CCO nanocomposite and consequently increase in the reversible specific capacity and coulombic efficiency. Different compositions of CNH foam with Co3O4 nanoparticles are prepared, among which the CCO 1:1 foam displays reversible capacity of 797 mAhg1 at current density of 0.1 Ag-1 along with excellent rate performance. High specific capacity of around 702 mAhg(-1) is obtained even at the current density of 5 Ag-1.
Keywords: 3D CCO foam; carbon nanohorns; Excellent rate capability; Li ion diffusion coefficient; Long Cycle life